Category Exemplar Production Norms for Hong Kong Cantonese: Instance Probabilities and Word Familiarity - Li, Bing; Lin, Qiduo; Mak, Hoi Yan; Tzeng, Ovid J. L.; Huang, Chih-Mao; Huang, Hsu-Wen (Frontiers in Psychology, 2021)
The lexical system of Hong Kong Cantonese has been heavily shaped by the local trilingual environment. The development of cultural- and language-specific norms for Hong Kong Cantonese is fundamental to understand how the speaker population organize semantic memory, how they utilize their semantic resources, and what information processing strategies they use for categorical semantic knowledge. This study presents a normative database of 72 lexical categories in Hong Kong Cantonese produced by native speakers in a category exemplar generation task. Exemplars are enlisted under a category label, along with the instance probabilities and word familiarity scores. Possible English equivalents are given to the exemplars for the convenience of non-HKC speaker researchers. Statistics on categories were further extracted to capture the heterogeneity of the categories: the total number of valid exemplars, the number of exemplars covering 90% of the occurrence of all valid entries, and the probabilities of the most frequent exemplars in each category. The database offers a direct lexical sketch of the vocabulary of modern Hong Kong Cantonese within a categorical structure. The category-exemplar lists, and the comparative statistics together lay the foundations for investigations in multiple fields and topics in the Hong Kong Cantonese speaking population, such as the structure of semantic knowledge, the time-course of knowledge access, and the processing strategies of young adults. The findings can be also used as a benchmark for other age groups. The database can serve as a crucial resource for establishing initial screening tests to assess the cognitive and psychological functioning of the Cantonese-speaking Hong Kong population in both educational and clinical settings. In sum, this normative study provides a fundamental resource for future studies on language processing mechanisms in Hong Kong population, as well as language studies and other cross-language/culture studies on Hong Kong Cantonese.